Remarks on Form and Temporality in Rondo I Wq. 57‎ by Carl Philipp Emanuel Bach - Mohammad, Iyad A. (Dirasat: Human and Social Sciences, 2025)
Objectives: The research aims at identifying the temporal structure that constitutes the C. Ph. E. Bach’s Rondo and determining the tools through which temporality operates on different structural levels. Methods: The research uses a descriptive-analytical phenomenological approach based on the notated musical text, where the method of development and unfolding of the musical piece over time is accurately described by detailing the various structural relationships in melody and tonality of its sections. Results: At the higher level of the musical structure, several parallel temporal frameworks are revealed: 1) the temporality of the rondo with its recurring refrains; 2) an overall tripartite form similar to that found in the sonata-rondo; 3) a cycle of repeated transitions using similar melodic elements in constantly changing configurations, along with recurring pauses and semi-cadential interruptions. At the mid-level, temporality manifests in the specific compositional technique used to produce new sound configurations from the ornaments and melodic elements in a continuous manner. Conclusions: The phenomenological description revealed temporality as a fundamental factor in the eventfulness and development of the musical composition, influencing the work at multiple structural and semantic levels.